2020
DOI: 10.1037/xlm0000780
|View full text |Cite
|
Sign up to set email alerts
|

Capitalization interacts with syntactic complexity.

Abstract: We investigated whether readers use the low-level cue of proper noun capitalization in the parafovea to infer syntactic category, and whether this results in an early update of the representation of a sentence's syntactic structure. Participants read sentences containing either a subject relative or object relative clause, in which the relative clause's overt argument was a proper noun (e.g., The tall lanky guard who alerted Charlie/Charlie alerted to the danger was young) across three experiments. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Perceptual inference asserts that sensory cues activate latent representations in the neural system that have been learned through experience. 4 In line with this idea, there is everaccumulating evidence that "lower level" cues like speech rate and phoneme perception (e.g., Kaufeld, Ravenschlag, Meyer, Martin, & Bosker, 2019;Kaufeld, Naumann, Meyer, Bosker, & Martin, 2019;Heffner, Dilley, McAuley, & Pitt, 2013;Dilley & Pitt, 2010), morphology (e.g., Gwilliams, Linzen, Poeppel, & Marantz, 2018;Martin, Monahan, & Samuel, 2017), foveal and parafoveally processed orthography (e.g., Cutter, Martin, & Sturt, 2019;Veldre & Andrews, 2018;Schotter, Angele, & Rayner, 2012), as well as "higher level" sentential (e.g., Kutas, Ferreira, & Martin, 2018;Martin & McElree, 2008van Alphen & Table 1.…”
Section: Linguistic Representation As Perceptual Inferencementioning
confidence: 99%
“…Perceptual inference asserts that sensory cues activate latent representations in the neural system that have been learned through experience. 4 In line with this idea, there is everaccumulating evidence that "lower level" cues like speech rate and phoneme perception (e.g., Kaufeld, Ravenschlag, Meyer, Martin, & Bosker, 2019;Kaufeld, Naumann, Meyer, Bosker, & Martin, 2019;Heffner, Dilley, McAuley, & Pitt, 2013;Dilley & Pitt, 2010), morphology (e.g., Gwilliams, Linzen, Poeppel, & Marantz, 2018;Martin, Monahan, & Samuel, 2017), foveal and parafoveally processed orthography (e.g., Cutter, Martin, & Sturt, 2019;Veldre & Andrews, 2018;Schotter, Angele, & Rayner, 2012), as well as "higher level" sentential (e.g., Kutas, Ferreira, & Martin, 2018;Martin & McElree, 2008van Alphen & Table 1.…”
Section: Linguistic Representation As Perceptual Inferencementioning
confidence: 99%
“…There were no significant effects or trends on the M atrix S ubject or V erb & A dverb regions. On the M atrix O bject region, there was a significant penalty for Subject conditions (M = 345 ms, SE = 13) over Object conditions (M = 308 ms, SE = 9), β = 0.043 (± 0.016), t = 2.685, p <.01, possibly due to an orthographic preview effect arising from the following R emnant region beginning in an uppercase letter in the Subject conditions (see Cutter et al 2019, for similar preview effects from capitalisation). There were no significant effects or trends in first pass times on the R emnant , S pillover or W rap - up regions.…”
Section: Resultsmentioning
confidence: 97%
“…Italicised labels correspond to analysis regions. Cutter et al 2019, for similar preview effects from capitalisation). There were no significant effects or trends in first pass times on the REMNANT, SPILLOVER or WRAP-UP regions.…”
Section: Tablementioning
confidence: 83%
“…As well as adding to a literature showing that readers assess the fit of a parafoveal word with preceding words in the sentence, our study also adds to a literature suggesting that people may sometime use (relatively) low-level information from words in order to assess their contextual fit. For example, Cutter et al (2020b) recently demonstrated that people may use initial-letter capitalisation as a cue that an upcoming word is a proper noun prior to completing lexical processing of that word. In our study readers were seemingly assessing whether word n + 2 was compatible with the preceding article on the basis of its orthographic form, with their being little chance that readers could have processed this word substantially enough for the effect to be postlexical.…”
Section: Discussionmentioning
confidence: 99%